2020
DOI: 10.1177/1941738120944254
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiotaping for the Rehabilitation of Rotator Cuff–Related Shoulder Pain: A Randomized Clinical Trial

Abstract: Background: Kinesiotaping (KT) has been widely used in clinical practice. Current evidence is insufficient to support the use of KT for treating rotator cuff–related shoulder pain (RCRSP), as its mid- and long-term effects have not been investigated. Hypotheses: Individuals using KT will achieve faster improvements in symptoms and functional limitations compared with those not using it. They will also present a greater increase in pain-free range of motion (ROM) and acromiohumeral distance (AHD) at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 47 publications
0
41
0
1
Order By: Relevance
“…Based on our sample size calculation, calculated for our primary outcome (Pain Interference subscale of the Brief Pain Inventory) using data from a pilot study on military members with MSKd [ 33 ], 15 participants per diagnosis will be required per group for a total of 120 participants (60 participants/group) (G*Power 3.1.7; α = 0.05, 1-β = 0.95, Baseline mean: 2.9+/− 1.5 points, Follow-up mean: 0.8+/− 1.2 points, expected lost at follow-up = 15% [based on past experiences with this population]. This number will enable us to determine the effects of the interventions for each of the four conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our sample size calculation, calculated for our primary outcome (Pain Interference subscale of the Brief Pain Inventory) using data from a pilot study on military members with MSKd [ 33 ], 15 participants per diagnosis will be required per group for a total of 120 participants (60 participants/group) (G*Power 3.1.7; α = 0.05, 1-β = 0.95, Baseline mean: 2.9+/− 1.5 points, Follow-up mean: 0.8+/− 1.2 points, expected lost at follow-up = 15% [based on past experiences with this population]. This number will enable us to determine the effects of the interventions for each of the four conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 109 studies were found through the electronic searches. Finally, 16 studies met our eligibility criteria and were included in the SR. 12,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The kappa agreement rate between reviewers was 0.91. The value represents only the 2% (approximately three studies) of discrepancy.…”
Section: Study Selectionmentioning
confidence: 99%
“…For the overall risk of bias, 52.9% of the clinical trials were rated as high risk of bias, 12,33,35,37,38,[40][41][42][43] 41.2% were rated as some concerns, [30][31][32]34,36,39 and 5.9% were rated as low risk of bias. 29 In the randomization process, 52.9% of the clinical trials were rated as high risk of bias. 12,32,33,35,37,[40][41][42] For the missing outcome data, 94.1% of the clinical trials were rated as low risk of bias.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakness or dysfunction of any RC or ST muscles may generate muscle imbalance which, in turn, may compromise kinematics and alter shoulder function [ 1 , 8 12 ]. Conservative rehabilitation programs, which commonly include strengthening and motor control exercises targeting RC (supraspinatus [SS], infraspinatus [IS]) and/or ST (upper trapezius [UT], middle trapezius [MT], lower trapezius [LT], serratus anterior [SA]) muscles, are known to be effective in reducing RCRSP-associated deficits and optimizing shoulder function [ 3 , 13 18 ].…”
Section: Introductionmentioning
confidence: 99%